Characteristics exponents of the triangular solution in the elliptical restricted three-body problem under radiating and triaxial primaries - Narayan, Ashutosh; Pandey, Krishna Kumar; Shrivastava, Sandip Kumar (International Journal of Advanced Astronomy, 2017)
This Paper deals with the effects of the radiation pressure and triaxiality of primaries on the stability of infinitesimal motion about triangular equilibrium points [ , ] in the elliptical restricted three body problem (ER3EB) around binary system. For determining the characteristic exponents of variational equations with periodic coefficient, we have used analytical method, described by Bennet in [3, 4]. This analytical method is based on Floquet’s theory. The stability of equilibrium points has been discussed under the assumption thatboth the primaries are radiating and triaxial. For this we have drawn transition cureves in μ-e plane. And it is seen that system is stable outside the transition curves, while system is Unstable within the transition curves.